Psychometric Evaluation of a Measure of Evidence-Based Practice in Occupational Health - Ruotsalainen, Jani; Päätalo, Kati; Martimo, Kari-Pekka; Oksanen, Tuula (La Medicina del Lavoro, 2024)
Background: Occupational Health Services (OHS) are obliged to follow the principles of evidence-based medicine. However, there needs to be tools to measure this. Therefore, we developed and validated a questionnaire for evaluating OHS practitioners’ attitudes, competence, and organisational support to perform evidence-based practice (EBP-OHS) following the JBI Model of Evidence-Based Healthcare. Methods: The questionnaire’s content validity was assessed by 12 experts in the field. Then, an opportunity sample of 549 OHS practitioners completed the questionnaire. We examined the questionnaire’s psychometric properties using exploratory factor analysis and subjected it to construct validity and reliability testing. Results: The content validity index of the chosen items was 0.78 or higher. Exploratory factor analysis revealed that the measure’s construct validity was adequate (KMO 0.9). Principal component factor analysis supported a three-factor structure (all eigenvalues 1.3 or more), which explained 60.3 % of the total variance. Aligned with these three factors, the EBP-OHS consists of three domains: Organisational support (seven items), OHS practitioners’ competence (six items) and OHS practitioners’ attitudes (two items). The scale’s reliability is good (Cronbach alpha 0.88). Conclusions: The EBP-OHS is a valid tool for measuring occupational health services’ evidence-based practice and enabling the implementation of research into practice. It embodies the phases of evidence transfer and implementation described in the JBI Model of Evidence-Based Healthcare and translates them into concrete measurable activities in the OHS context.